2011
DOI: 10.3109/01443615.2011.598967
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cervical squamous intraepithelial lesions among HIV-positive women in Enugu, South-eastern Nigeria

Abstract: HIV infection is a risk factor for cervical cancer and both diseases are prevalent in Nigeria. The study determined the prevalence of cervical squamous intraepithelial lesion (SIL) among HIV-positive women in Enugu state, which has the highest HIV burden in South-eastern Nigeria. Pap smear was carried out on 150 HIV-positive (HIV+ve) women and 150 HIV-negative (HIV?ve) controls at the University of Nigeria Teaching Hospital, Enugu, Nigeria from December 2007 to March 2008. The prevalence of SIL for the HIV+ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 13 publications
4
20
6
Order By: Relevance
“…Out of the 65 HIV positive women screened for premalignant cervical lesions,17 (26.2%) had abnormal cytology result which is higher than 11 (16.9%) among the control group though this was not statistically significant. This prevalence is higher than 12.6% and 4.6% found by Dim et al [27] among HIV positive and HIV negative women respectively. Ezechi et al [28] also found a similar prevalence with Dim, 14.3% and 3.3% among HIV positive and negative women respectively.…”
Section: Prevalence Of Premalignant Cervical Lesions Among Respondentscontrasting
confidence: 55%
“…Out of the 65 HIV positive women screened for premalignant cervical lesions,17 (26.2%) had abnormal cytology result which is higher than 11 (16.9%) among the control group though this was not statistically significant. This prevalence is higher than 12.6% and 4.6% found by Dim et al [27] among HIV positive and HIV negative women respectively. Ezechi et al [28] also found a similar prevalence with Dim, 14.3% and 3.3% among HIV positive and negative women respectively.…”
Section: Prevalence Of Premalignant Cervical Lesions Among Respondentscontrasting
confidence: 55%
“…It is however lower than 68.3 and 43.7% prevalence rates reported in Jos, Nigeria by Agaba et al (2009) and in Kenya by Mabeya et al (2012). A lower rate of 12.6% was reported in Enugu by Dim et al (2011).…”
Section: Discussioncontrasting
confidence: 43%
“…Several studies in Nigeria have found an association between cervical cancer and HIV [47,55]. A registry linkage study in Nigeria reported a twofold higher risk of cervical cancer in people living with HIV/AIDS [31].…”
Section: Discussionmentioning
confidence: 99%